THE EFFECT OF CASHEW NUT PUREE ON THE PHYSICOCHEMICAL AND ORGANOLEPTIC CHARACTERISTICS OF SOY MILK ICE CREAM FOR LACTOSE INTOLERANCE SUFFERERS - Audry Azzahra Ikhsan; Kejora Handarini; Retnani Rahmiati; Dewi Mariyanah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Soy milk ice cream is an alternative food product for those with lactose intolerance who cannot consume cow's milk. The addition of cashew nut puree increases the fat content and improves the texture of the ice cream, making it smoother and creamier. This study aims to determine the effect of variations in cashew nut puree concentration on the physicochemical and organoleptic properties of soy milk ice cream. This study used a laboratory experimental method with a completely randomized design (CRD) with one factor consisting of four treatment levels, namely the addition of cashew nut puree of 0%, 10%, 20%, and 30%, each with three replications . The parameters observed included physicochemical properties consisting of protein, fat, overrun, melting speed, total solids, and organoleptic tests (color, aroma, taste, and texture). The results showed that the addition of cashew nut puree had a significant effect (p <0.05) on the physicochemical and organoleptic properties of soy milk ice cream. The treatment with the addition of 30% cashew nut puree showed the highest values in protein, fat, and total solids levels, and produced a slower melting speed and a higher level of sensory acceptance compared to other treatments. Although the highest overrun value was obtained in the treatment with the addition of 20% cashew nut puree, increasing the concentration of cashew nut puree to 30% generally resulted in an increase in the physicochemical quality and organoleptic characteristics of non-dairy soy milk ice cream.